EFFECT OF FORCES ON AIR CONVEYING DEVICES AND NETWORK ON COTTON SEED QUALITY - Shodiev Ziyodullo Ochilovich; Duskaraev Nortaylok Abduganievich; Shodiev Sadir Nematovich; Shodiev Nematjon Sadirovich (Galaxy International Interdisciplinary Research Journal, 2021)
One of the most important requirements for the transportation of seed cotton is the quality of the flour. Therefore, most researchers focus on the study of seed damage, because it affects the quality of the finished product, the fiber is slipped into the technologist spinning properties.